The acceptance and use of mobile learning for Kuwaiti government employee training: views from the perspectives of UTAUT - Alajmi, Nada; Md. Khambari, Mas Nida; Abdrahim, Nur Aira; Wong, Su Luan (Human Resources Management Academic Research Society (HRMARS), 2024)
With the rapid advancements of technology, Kuwait is one of the countries taking on the efforts to implement mobile learning strategies for employee training. By leveraging the Unified Theory of Technology Acceptance and Use (UTAUT), this study centers on the acceptance and use of mobile learning for Kuwaiti Government employee training. A qualitative approach was used in a case study on Kuwait's public sector personnel, focusing on the Kuwait Civil Service Commission’s (KCSC) eTraining initiative since 2008, involving interviews with ten employees. The study reveals that workplace mobile learning acceptance and use are influenced by employees' digital skills, mobile learning infrastructure, resources, and workplace standards and policy. Employees obtained specialized information and abilities necessary for their job through deliberate learning activities outlined in the mobile learning standards and rules. The implementation of a comprehensive mobile learning infrastructure and the utilization of advanced hardware have significantly enhanced the efficacy of technology in the workplace. The results of the study highlighted the significance of digital skills in the workplace in relation to mobile learning aspects and job demands. This study has provided significant insights for the public sector in Kuwait, considering the scarcity of existing research on this subject matter.